Respostas

2014-01-17T11:39:19-02:00
x²-2x-3=0

Δ = (-2)² -4.1.(-3) 
Δ = 4-(-12)
Δ = 16

x = -(-2)+ - 4  / 2.1
x = 2 + - 4 / 2
x'  = 2 + 4/ 2 = 6 / 2 = 3
x" = 2 - 4 / 2 = -2/ 2 = - 1

então x" < x'  , x" é o primeiro termo e x' o segundo 

a ) 
(-1, 3, ...)
    r = a2 - a1  
    r = 3 - (-1)
    r = 4 

a razão é 4 

b ) 
a12 = a2 + 10r
     a12 = 3 + 10(4)
     
a12 = 3 + 40
     a12 = 43

o 12º é 43 
2 5 2
2014-01-17T11:47:55-02:00
X²-2x-3=0

a=1 b=-2 c=-3

Δ=b²-4ac
Δ=(-2)²-4.1.(-3)
Δ=4+12
Δ=16

x=-b+-√Δ/2a
x=-(-2)+-√16/2.1
x=4+-4/2

x'=4-4/2 = 0/2 =0
x''= 4+4/2 = 8/2 = 4


a) razão :
  4-0 = 4

b)12º termo :
An=A1+(n-1).r
An=0+(12-1).4
An=(11).4
An=44
1 4 1